(untitled) (Journal of Educational Sciences, 2025)
Amid the rapid sociocultural transformations of modern Kazakhstan, the issue of developing the moral consciousness of youth acquires not only pedagogical but also national strategic significance. This study is devoted to a deep theoretical and empirical analysis of educational practices that contribute to the formation of students’ moral values within the higher education system. Particular attention is paid to the potential of the state programs “Rukhani Zhangyru” and “Adal Azamat” as ideologically and axiologically rich foundations for designing an effective educational environment. The aim of the study was to conduct a scholarly analysis of educational practices that facilitate the development of moral consciousness among university students in Kazakhstan, using Zhetysu University named after I. Zhansugurov as a case study. The research encompassed a review of theoretical approaches to morality in education, an analysis of the program content from a pedagogical perspective, and an identification of practical implementation barriers. The methodological framework incorporated both quantitative and qualitative methods: student surveys, semi-structured interviews with faculty members, content analysis, and thematic interpretation. The empirical base included 217 students and 12 instructors at Zhetysu University. To assess the reliability of the questionnaire scales, Cronbach’s alpha coefficient was calculated (α = 0.79), indicating the statistical robustness of the research tool. The main findings revealed a high level of students’ formal awareness of the program, but a low level of personal value internalization. The proposed model—based on activity-based, axiological, and reflexive approaches—proved effective during testing, showing an increase in the number of students consciously aligning their moral positions with the values of the program. The scientific novelty of the study lies in reinterpreting a state ideological initiative as a tool for ethical education within a secular academic environment. The practical significance of the research is reflected in the potential integration of the model into the educational programs of Kazakhstani universities and its application in the training of instructors and academic advisors. Key words: moral consciousness, values, student youth, educational work, Rukhani Zhangyru, axiology.